2002
DOI: 10.1103/physrevb.65.172102
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin-scattering study of the broad doublet in isotopically exchangedSrTiO3

Abstract: A comparative Brillouin-scattering study of the broad doublet and acoustic phonons in isotopically substituted SrTi( 18 O 1Ϫx 16 O x ) 3 and ''pure'' SrTi 16 O 3 crystals is presented. The acoustic-phonon frequency is found to decrease as a result of the substitution, but the doublet spectra above 20 K show no obvious differences. The results are examined in connection with the second-sound interpretation of the doublet. Influence of the phase transition on the doublet spectra is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…One might think that this could be the reason why the BD intensity became weak in STN. However, the BD has been clearly observed in an isotope exchanged sample SrTi( 18 O 1−x 16 O x ) 3 : x = 0.403, where 18 O atoms are impurities for the STO16 matrix [8]. Moreover, the exchange ratio of Nb to Ti is only about 0.0024 at most in our STN sample and is quite small in comparison with 0.403.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…One might think that this could be the reason why the BD intensity became weak in STN. However, the BD has been clearly observed in an isotope exchanged sample SrTi( 18 O 1−x 16 O x ) 3 : x = 0.403, where 18 O atoms are impurities for the STO16 matrix [8]. Moreover, the exchange ratio of Nb to Ti is only about 0.0024 at most in our STN sample and is quite small in comparison with 0.403.…”
Section: Resultsmentioning
confidence: 64%
“…Since the frequency of the BD is much lower than that of a transverse acoustic mode of lowest frequency, the physical origin of the BD comes to attract attention. Hehlen [7][8][9]. Although these researchers concluded that the physical origin of the BD is not the second sound, no one has proposed any other candidate for the origin.…”
Section: Introductionmentioning
confidence: 99%
“…Heat anomaly due to ferroelectric phase transition at T c has not been detected at the present time, perhaps because the atom's displacement is too small to produce a detectable heat anomaly. Plausible reasons for the existence of a clear phase transition are that (1) transverse acoustic c 44 mode splits into two modes at T c [27][28][29], (2) Raman spectra indicate ferroelectric soft mode above and below T c [23,30], (3) linear birefringence [26] measured along [001] tetra shows a clear evidence of biaxiality of the crystal below T c , and (4) pressure dependence of T c (Fig. 7) suggests the existence of phase transition (dT c /dp ≈ ∞, at T = 0 K).…”
Section: Resultsmentioning
confidence: 98%
“…In the case of centralpeak behavior at low T , important features that can now be examined in more detail include the broad doublet component appearing in the Brillouin scattering spectra of SrTiO 3 at low temperatures [2][3][4]. The origin of the doublet has been a subject of substantial controversy [2][3][4][5][6], discussed often in terms of the second sound and two-phonon difference scattering. Brillouin scattering study of the broad doublet in the isotopically exchanged SrTi 18 O 1−x 16 O x can provide the means for an enlightening comparison of the doublet feature in SrTiO 3 and help to clarify its possible origin.…”
Section: Introductionmentioning
confidence: 97%